Poesia - Sarmiento Rojas, Karina (Revista Entrelíneas, 2019)
Karina Sarmiento Rojas Paula Andrea Ortiz Ruiz Sandra Marcela Cárdenas Prieto Mayeli Enriquez Muñoz Juan Pablo Cañas Sánchez José Antonio Trujillo Castro Ángelo cruz